POTRET KEMISKINAN DI INDONESIA (ANALISIS PERAN NEGARA DALAM MENANGGULANGI KEMISKINAN) - Fitria Karnudu (IAIN Ambon, 2017)
One of the important agenda given special attention to the government, is to improve people's welfare. This is reasonable considering the low level of welfare of the majority of the Indonesian people. That is because the government policies also influence the increase in poverty in Indonesia. In addition, programs to reduce poverty, the government implement populist programs, such as direct cash assistance, Jamkesnas, PNPM Mandiri, and rice for the poor, have not been able to reduce poverty significantly. Therefore, the government should conduct a policy more comprehensive, systematic, and not temporary, so slowly poverty in Indonesia can be reduced. Keywords: the role of the state, prevention, poverty